Identification of the molecular mechanism of christinin compounds from Arabian bidara leaves (Ziziphus spina-christi L.) on microorganisms that cause female genital problems through computational approaches - Fitrianti Darusman; Taufik Muhammad Fakih (Universitas Ahmad Dahlan, 2020)
Arabian bidara leaves (Ziziphus spina-christi, L.) are known to have strong antimicrobial activity against microorganisms that cause infection in the female genital area, namely Staphylococcus aureus bacteria and Candida albicans fungi. They contain main secondary metabolites such as flavonoids, alkaloids, and saponins. Christinin is a saponin glycoside derivative compound which consists of four types, namely christinin-A, B, C, and D. The role of computational studies in the discovery of new drugs is crucial and interesting nowadays because it is relatively cheap, effective, fast, and precise with a reliable level of accuracy. This computational study result will later be used to confirm in vitro test results which are carried out using experimental microbiological testing methods in the laboratory. This study identified, evaluated, and explored the interactions between christinin-A, B, C, and D compounds with Penicillin Binding Protein (PBP) from Staphylococcus aureus and Dihydrofolate Reductase from the fungus Candida albicans using computational study were carried out using the molecular docking. The christinin-A, B, C, and D compounds were modeled into 3D conformation using GaussView 5.0.8 and Gaussian09 software. The best conformation was selected for molecular interaction studies on Penicillin Binding Protein (PBP) from Staphylococcus aureus bacteria and Dihydrofolate Reductase from Candida albicans using MGLTools 1.5.6 software with AutoDock 4.2. The molecular interactions that occurred were further observed using the BIOVIA Discovery Studio 2020 software. Based on the molecular docking results, the christinin-B compound had the highest affinity for Penicillin Binding Protein (PBP) from Staphylococcus aureus bacteria, with a binding-free energy value of âˆ’7.67 kcal/mol. Meanwhile, the christinin-A compound has the highest affinity for Dihydrofolate Reductase from the fungus Candida albicans, with a binding-free energy value of âˆ’8.38 kcal/mol. Thus, it is predicted that christinin compounds can be chosen as the main component in feminine hygiene preparations to maintain the female genital area's health.Â